Gamma radiation-induced graft copolymerization of styrene onto poly(ethyleneTerephthalate) films - Nasef, Mohamed Mahmoud (John Wiley & Sons, Inc., 2000)
Gamma radiation-induced graft copolymerization of styrene onto poly(ethylene terephthalate) (PET) films was studied using simultaneous irradiation technique. The effects of grafting conditions on the degree of grafting were investigated. The grafting conditions include monomer concentration, irradiation dose, dose rate, and the type of solvent. Moreover, the effect of the addition of crosslinking agents [i.e., divinylbenzene (DVB) and triallyl cyanurate (TAC)] having various concentrations were also investigated. The degree of grafting was found to be greatly dependent on the grafting conditions. Of the three diluents employed, methylene chloride was found to drastically enhance the degree of grafting. The order of dependence of the initial rate of grafting on the monomer concentration was found to be 2.2. The grafted PET films were identified by FTIR spectroscopy and characterized by X-ray diffraction (XRD).